Penguatan Peran Masyarakat Lokal dalam Pengelolaan Wisata Pantai Bahari Monano melalui Pendekatan Partisipatif - Paweni, Linawati; Nuna, Muten S; Tjokra, Muhamad R; Biongan, Ahiar; Tabo, Sarfan (Jurnal Publisitas, 2025)
The Monano Marine Tourism Beach, located in Monano District, North Gorontalo Regency, is an area with significant potential to be developed into a leading tourist destination. However, its management still faces various challenges, such as lack of coordination between managers and the community, inadequate supporting facilities, and the absence of integration of local values into tourism activities. This study aims to analyze tourism governance management based on community participation using the four functions of management: planning, organizing, actuating, and controlling. Additionally, the research identifies the factors that hinder community involvement in managing the tourism area. This study employs a descriptive qualitative method, using data collection techniques such as observation, in-depth interviews, and documentation. Informants include representatives from the Tourism Office, village government, local communities, and tourists. The findings reveal that planning has not actively involved the community, organizing lacks a formal structure such as the Pokdarwis (Tourism Awareness Group), actuating remains informal, and controlling is conducted voluntarily without a structured system. Key inhibiting factors include limited budget, low community capacity, insufficient tourism infrastructure, and weak integration of local cultural values. Based on the research findings, it is recommended that tourism management at Monano Marine Tourism Beach focus on establishing an official institutional structure such as Pokdarwis to systematically accommodate community participation. The local government should also increase budget allocation and provide technical support for the development of adequate tourism facilities. Moreover, training and mentoring for local communities are crucial to enhance their capacity in independently managing tourism potential. The integration of local cultural values into tourism programs also needs to be strengthened to reinforce the area’s identity and broaden its appeal to tourists